2020
DOI: 10.1007/s00280-019-04014-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, single-dose study to evaluate the biosimilarity of QL1101 with bevacizumab in healthy male subjects

Abstract: Purpose This is the first study to compare the pharmacokinetics of QL1101, a proposed bevacizumab biosimilar, with Avastin ® sourced from Roche Diagnostics GmbH. Methods In this double-blind, single-dose, parallel-group study, healthy male subjects were randomized 1:1 to receive QL1101 or Avastin ® 3 mg/kg intravenously. Pharmacokinetic assessments were conducted for 85 days, with additional safety and immunogenicity assessments until day 90. Primary study endpoints were area under the concentration-time curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
(25 reference statements)
6
11
0
Order By: Relevance
“…Moreover, results confirm that bevacizumab-EU and bevacizumab-US are bioequivalent to each other, consistent with results from other phase I studies of bevacizumab biosimilars [16,17]. The PK results of this study are consistent with those of other phase I PK studies of (proposed) bevacizumab biosimilars which also demonstrated equivalence to the reference product [16][17][18][19][20][21][22][23][24][25][26]. However, direct comparisons of absolute PK parameters values between studies are generally not appropriate due to differences between the doses used (1 mg/kg, 3 mg/kg or 5 mg/kg), sample collection, and assessment methods [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, results confirm that bevacizumab-EU and bevacizumab-US are bioequivalent to each other, consistent with results from other phase I studies of bevacizumab biosimilars [16,17]. The PK results of this study are consistent with those of other phase I PK studies of (proposed) bevacizumab biosimilars which also demonstrated equivalence to the reference product [16][17][18][19][20][21][22][23][24][25][26]. However, direct comparisons of absolute PK parameters values between studies are generally not appropriate due to differences between the doses used (1 mg/kg, 3 mg/kg or 5 mg/kg), sample collection, and assessment methods [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 89%
“…The mean t 1/2 of HOT-1010 and Avastin ® was 14.6 d and 14.9 days, which was consistent with the results of other bevacizumab biosimilars (13.1-19.3 days) in Chinese, Indian, Caucasian and Korean healthy male subject studies (Knight et al, 2016;Zhang et al, 2018;Wang et al, 2019;Liu et al, 2020;Shin et al, 2020;Singh et al, 2020). The median T max of HOT-1010 (3.48 h) was similar to that of bevacizumab and other bevacizumab biosimilars (2.5-4.5 h) when intravenous dose ranged from 1 to 3 mg/kg (Zhang et al, 2018;Wang et al, 2019;Liu et al, 2020;Shin et al, 2020;Singh et al, 2020). HOT-1010 was well-tolerated and no safety concerns were identified, and safety profiles were similar between HOT-1010 group and Avastin ® group.…”
Section: Discussionsupporting
confidence: 84%
“…The most common TEAEs (more than 5% incidence) included increased blood triglycerides, increased alanine aminotransferase, increased aspartate aminotransferase, hyperuricemia, decreased blood fibrinogen, increased conjugated bilirubin, increased blood creatine phosphokinase and proteinuria. TEAEs reported in this study were almost expected, based on previous studies in healthy subjects and tumor patients (Genentech Inc, 2015;Liu et al, 2020;Wang et al, 2019). All subjects with TEAEs had recovered.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Since NMPA launched “Guidelines for the research, development and technique assessment of biosimilar drugs (Trial)” in 2015 [15] , 49 trials involving bevacizumab biosimilars have emerged. QL1101 (ChiCTR1900022767) [40] and IBI305 (NCT02954172) [41] were approved by NMPA on Dec 18th, 2019 and June 19th, 2020, respectively.…”
Section: Discussionmentioning
confidence: 99%